Supreme faith : someday we'll be together - Wilson, Mary.; Romanowski, Patricia (New York : Harper & Row Publishers, Inc., 1990)
A gutsy follow-up to Wilson's blockbuster, Dream girl, which has sold half a million copies in paper and cloth. Picking up where that bestseller left off, Wilson details life at Motown after Diana Ross quit the Supremes and describes Ross' horror as the Supremes racked up top-ten hits while her singles went nowhere.
Keywords: AUTOBIOGRAPHIES